Dynamic-stability improvement of a multi-machine power system connected with a large-scale offshore wind farm using a generalized inified power flow controller
Chapter 1 Introduction; Chapter 2 Configuration of the system; Chapter 3 Design of oscillation damping controllers for GUPFC; ...